2014
DOI: 10.4103/2231-0762.142024
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliative cytology of buccal squames: A quantitative cytomorphometric analysis of patients with diabetes

Abstract: Background:Diabetes is a third leading cause of mortality and morbidity in the world. Diabetes is one of the most common endocrine metabolic disorders and its prevalence has been increasing worldwide. Oral exfoliative cytology may be a more appropriate adjunctive diagnostic tool in conditions like diabetes mellitus, where the invasive techniques lose viability.Aims:The purpose of this study is to analyze the cytomorphometric changes in the exfoliated cells of the oral mucosa, as an adjunct to the diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Due to this epithelial cells show cellular adaption, depicted as nucleus hypertrophy with more DNA content as compared to normal cells. 22 In another study it was investigated on both the type 1 and type 2 diabetic patients and it was concluded that both the quantitative and qualitative cytomorphometric changes occurred in the oral mucosa. The type and pathophysiology of diabetes either type 1 or type 2 do not alter the effect on these cytomorphometric changes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this epithelial cells show cellular adaption, depicted as nucleus hypertrophy with more DNA content as compared to normal cells. 22 In another study it was investigated on both the type 1 and type 2 diabetic patients and it was concluded that both the quantitative and qualitative cytomorphometric changes occurred in the oral mucosa. The type and pathophysiology of diabetes either type 1 or type 2 do not alter the effect on these cytomorphometric changes.…”
Section: Discussionmentioning
confidence: 99%
“…As per a study conducted by Sankhla et al (2014), diabetes has an impact on the morphology of oral mucosa, potentially resulting in compromised tissue repair and retardation of tissue growth. The use of cytomorphometric analysis on cells obtained from diabetic patients holds promise as a non-invasive diagnostic tool.…”
Section: Discussionmentioning
confidence: 95%
“…The buccal smear is a simple test in which mucosal cells are taken from the cheek, and these cells can be used for the investigation of the cellular effects of risk factors including bacterial, fungal, and viral infections, hormonal changes, immune system changes, diabetes mellitus and iron deficiency anaemia, neoplasms, radiotherapy, chemotherapy, alcohol and smoking, as well as genetic testing 3‐11 . We postulated that the evaluation of buccal smears might be a suitable approach for investigating of the impact of prematurity on neonates.…”
Section: Introductionmentioning
confidence: 99%